2006
DOI: 10.1111/j.1748-5827.2006.00063.x
|View full text |Cite
|
Sign up to set email alerts
|

Subtotal intracapsular prostatectomy as a useful treatment for advanced‐stage prostatic malignancies

Abstract: It was concluded that, in the authors' facility, treatment of prostatic cancer by subtotal intracapsular prostatectomy was superior to that by total prostatectomy, with respect to both postoperative survival and serious complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
29
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 7 publications
3
29
0
1
Order By: Relevance
“…The signalment and clinical presentation of dogs in the present study was similar to previous reports of dogs with prostatic tumors . Total prostatectomy has been associated with an unacceptably high complication rate in previous studies in dogs . However, the majority of these studies included total prostatectomy for treatment of various prostatic diseases, and only 1 publication, specifically focused on prostatic neoplasia, reported short survival times (range, 5‐45 days).…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…The signalment and clinical presentation of dogs in the present study was similar to previous reports of dogs with prostatic tumors . Total prostatectomy has been associated with an unacceptably high complication rate in previous studies in dogs . However, the majority of these studies included total prostatectomy for treatment of various prostatic diseases, and only 1 publication, specifically focused on prostatic neoplasia, reported short survival times (range, 5‐45 days).…”
Section: Discussionsupporting
confidence: 84%
“…Total prostatectomy has been associated with an unacceptably high complication rate in previous studies in dogs . However, the majority of these studies included total prostatectomy for treatment of various prostatic diseases, and only 1 publication, specifically focused on prostatic neoplasia, reported short survival times (range, 5‐45 days). Although this study did not disclose the incidence of postoperative urinary incontinence, other studies have identified this condition as the most common complication after total prostatectomy, affecting 33%‐100% of operated dogs .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mandibulectomies and simple wound reconstructions with skin flaps are carried out increasingly in general practice although more specialist procedures such as maxillectomies, rib resections, limb salvage operations, total pelvic osteotomies etc are probably almost exclusively carried out by referral institutions. Surgical techniques carried out at referral institutions and present in this issue include tracheal resection (Mahler and others 2006), keratectomy/sclerectomy (Donaldson and others 2006) and subtotal intracapsular prostatectomy, as well as total prostatectomy (Vlasin and others 2006).…”
mentioning
confidence: 99%